2013
DOI: 10.4172/2157-7048.1000155
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Tataouines Raw and Activated Clay

Abstract: This study deals with the mineralogical and thermal analysis of red clay taken from the south of Tunisia (Tataouine area) which will be used in industrial and environmental fields. In that purpose the study had recourse to several quantitative and qualitative research instruments: chemical analysis, mineralogical study and thermal analysis. The analyses were carried out by different methods such as: (i) X-ray diffraction (XRD), (ii) infrared spectroscopy (IR), (iii) thermogravimetric analysis (TGA), (iv) diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This indicates the release of Al 3+ , Mg 2+ and Fe 3+ cations from the octahedral sheets. The obtained results accord well with those in the previous studies 27–47 and confirm the chemical found analyses.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates the release of Al 3+ , Mg 2+ and Fe 3+ cations from the octahedral sheets. The obtained results accord well with those in the previous studies 27–47 and confirm the chemical found analyses.…”
Section: Resultssupporting
confidence: 92%
“…The infrared analyses of the untreated and activated clays are illustrated in Figure 5 to evaluate the influence of the acid treatments on clay material. As can be seen from the spectra of untreated clay (A) the adsorption bands at 3637.61 and 915.1 cm −1 attributed to stretching vibrations Al‐Al‐OH and deformation vibration Al‐OH‐Al, respectively, indicate that this clay is dioctahedral 45,46 . The bands at 840.16 cm −1 , 872 cm −1 can correspond to Al‐Mg‐OH and Al‐Fe‐OH.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Due to acid activation, the pH decreased from 8.5 to 3.8. The results indicate the AMKC would be good enough to eliminate metal ions at pH > 3.8 [ 54 ]. A basic idea, samples develop positive charge when the pH of substance is lesser than the pH pzc .…”
Section: Resultsmentioning
confidence: 99%
“…Some exchangeable cations were replaced during the activation by H + from sulfuric acid and by CTA + from cetyltrimethyl ammonium. In order to balance the negatively charged clay surfaces, the latter attract exchangeable positive ions contained in the solutions [38]. The CEC was reduced by pH treatment [39], and elements can also be released from the octahedral sheet [40].…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 99%